2012
DOI: 10.1371/journal.pone.0034107
|View full text |Cite
|
Sign up to set email alerts
|

HDL Proteome in Hemodialysis Patients: A Quantitative Nanoflow Liquid Chromatography-Tandem Mass Spectrometry Approach

Abstract: Aside from a decrease in the high-density lipoprotein (HDL) cholesterol levels, qualitative abnormalities of HDL can contribute to an increase in cardiovascular (CV) risk in end-stage renal disease (ESRD) patients undergoing chronic hemodialysis (HD). Dysfunctional HDL leads to an alteration of reverse cholesterol transport and the antioxidant and anti-inflammatory properties of HDL. In this study, a quantitative proteomics approach, based on iTRAQ labeling and nanoflow liquid chromatography mass spectrometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
63
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 41 publications
4
63
0
1
Order By: Relevance
“…When associated with HDL, Hb also likely acts as an antioxidant and may mediate HDL transport of iron. Hb is not the only iron-binding protein on HDL, as serotransferrin is also highly abundant on HDL and was recently found to be decreased on HDL after hemodialysis in patients with end-stage renal disease ( 79 ). HDL likely participates in the transport of iron from the gut and phagocytic cells to targeted recipient cells through serotransferrin and thus contributes to global homeostasis and cellular metabolism and physiology.…”
Section: Hdl Proteomementioning
confidence: 99%
“…When associated with HDL, Hb also likely acts as an antioxidant and may mediate HDL transport of iron. Hb is not the only iron-binding protein on HDL, as serotransferrin is also highly abundant on HDL and was recently found to be decreased on HDL after hemodialysis in patients with end-stage renal disease ( 79 ). HDL likely participates in the transport of iron from the gut and phagocytic cells to targeted recipient cells through serotransferrin and thus contributes to global homeostasis and cellular metabolism and physiology.…”
Section: Hdl Proteomementioning
confidence: 99%
“…The number of proteins identified was somewhat smaller than what has previously been achieved using iTRAQ labeling [17]. However, all proteins reliably identified and quantified by iTRAQ in our study have been shown to belong to the HDL proteome, and they represent the most abundant proteins found in this fraction [17,18,19,20,21,22]. …”
Section: Discussionmentioning
confidence: 56%
“…Recent reports have shown that HDL-C may be a biomarker for diseases like psoriasis (Holzer et al 2012), rheumatoid arthritis (Raterman et al 2013), and liver fibrosis in hepatitis C patients (Gangadharan et al 2012). Alterations in HDL composition have been observed also in hemodialysis patients (Mangé et al 2012). Special interest has been recently focused on HDL in cancer patients.…”
Section: Hdl Cholesterol As a Risk Factor For Other Diseasesmentioning
confidence: 99%